FSL constructs: a simple method for modifying cell/virion surfaces with a range of biological markers without affecting their viability - Blake, DA; Bovin, NV; Bess, D; Henry, SM (Journal of Visualized Experiment, 2011)
The ability to modify/visualize biological surfaces, and then study the modified cell/virion in a range of in vitro and in vivo environments is essential to gaining further insight into the function of specific molecules or the entire entity. Studies of biological surface modification are generally limited to genetic engineering of the organism or the covalent attachment of chemical moieties to the cell surface 1,2. However these traditional techniques expose the cell to chemical reactants, or they require significant manipulation to achieve the desired outcome, making them cumbersome, and they may also inadvertently affect the viability/functionality of the modified cell. A simple method to harmlessly modify the surface of cells is required. Recently a new technology, KODE Technology has introduced a range of novel constructs consisting of three components: a functional head group (F), a spacer (S) and a lipid tail (L) and are known as Function-Spacer-Lipid or FSL constructs3. The spacer (S) is selected to provide a construct that is dispersible in water, yet will spontaneously and stably incorporate into a membrane. FSL construct functional moieties (F) so far include a range of saccharides including blood group-related determinants, sialic acids, hyaluronan polysaccharides, fluorophores, biotin, radiolabels, and a range of peptides 3-12. FSL constructs have been used in modifying embryos, spermatozoa, zebrafish, epithelial/endometrial cells, red blood cells, and virions to create quality controls systems and diagnostic panels, to modify cell adhesion/ interaction/ separation/ immobilization, and for in vitro and in vivo imaging of cells/virions 3-12. The process of modifying cells/virions is generic and extremely simple. The most common procedure is incubation of cells (in lipid free media) with a solution for FSL constructs for 1-2 hours at 37°C4-10. During the incubation the FSL constructs spontaneously incorporate into the membrane, and the process is complete. Washing is optional. Cells modified by FSL constructs are known as kodecytes 6-9, while virions are Kodevirions 10. FSL constructs as direct infusions and kodecytes/kodevirions have been used in experimental animal models 7,8,10. All kodecytes/kodevirions appear to retain their normal vitality and functionality while gaining the new function of the F moiety 7,8,10,11. The combination of dispersibility in biocompatible media, spontaneous incorporation into cell membranes, and apparent low toxicity, makes FSL constructs valuable research tools for the study of cells and virions.